Peranan dan Fungsii Ombudsman Ri Perwakilan Sumatera Barat dalam Mencegah Maladministrasi - Hadijah, Awan; Puspita, Riri; Syafril, Rizki (Jurnal Ilmu Manajemen, Bisnis dan Ekonomi, 2024)
Maladministration is a problem that can threaten community welfare and the quality of public services. The Ombudsman of the Republic of Indonesia (RI) acts as an institution tasked with supervising public services and preventing maladministration. In the context of West Sumatra, the Indonesian Ombudsman Representative for West Sumatra has an important role in maintaining the integrity and accountability of a regional government. This article aims to analyze the role and function of the Indonesian Ombudsman Representative for West Sumatra in preventing maladministration. In this research study, researchers applied qualitative descriptive methods. And researchers collected data through interview methods with several sources. The findings of this research describe how the Indonesian Ombudsman Representative for West Sumatra carries out the role and function of preventing maladministration in the delivery of public services, based on the principles and standards in the Public Service Law.